Antifungal activity and mechanism of carvacrol against Fusarium graminearum with damaging cell membranes and affecting energy metabolism - Xuewei Mao; Xingchen Zhao; Tangbo Cao; Liting Chen; Qinqin Wang; Lin Zhou (Pesticide Biochemistry and Physiology, 2026)

Disrupting cytomembrane function mediates the antifungal activity of carvacrol against Sclerotium rolfsii - Liting Chen; Xingchen Zhao; Tangbo Cao; Qinqin Wang; Meizi Wang; Jingjing Zhang; Xuewei Mao; Yun Duan; Lin Zhou (Pesticide Biochemistry and Physiology, 2026)

Pilot-scale tests on struvite recovery from agricultural wastewater: the effects of seeding, growth kinetics, and crystallization mechanisms - Ruizhu Hu; Xingchen Liu; Ziqi Lin; Tinglin Huang; Gang Wen; ShouQing Ni (Chemical Engineering Journal, 2025)

The role of RANBP1 in regulating MiRNA expression and apoptosis in breast cancer cells - Pengxia Song; Lin Zhang; Huiping Qiu; Xingchen Zhou; Yanhui Cao; Jie Liu; Xin Zheng; Yubin Liu; Shuihong Yao (Genes & Genomics, 2025)
Background Breast cancer poses a huge health threat in China. Emerging evidence has indicated that RANBP1 is associated with poor prognosis of breast cancer and has been shown to influence miRNA expression in colorectal cancer. But its role in breast cancer remains unclear. Objective The purpose of this research is to construct the sh-RANBP1 cell line derived from a human breast cancer cell line in order to investigate the impact of low RANBP1 expression on the expression network of breast cancer-associated miRNAs and mRNAs. Methods We constructed the sh-RANBP1 cell line from the human breast cancer cell line MDA-MB-231 and analyzed the significant differential expression between the two groups using miRNA sequencing and mRNA sequencing of both the sh-RANBP1 group and the control group. The differential miRNA-mRNA regulatory network for the two groups was established by intersecting target predictions with the differential expression data. The results were further verified using Western blotting (WB), quantitative PCR (qRT-PCR), and flow cytometry. Results In this study, we compared the expression levels of miRNA and mRNA between the sh-RANBP1 group and the control group. Our findings indicate that sh-RANBP1 influences miRNA expression, revealing significant differences based on the interaction network of miRNA and mRNA. The genes involved are associated with pathways such as apoptosis. Subsequent WB and qRT-PCR results further validated our findings. Finally, flow cytometry confirmed an increased proportion of apoptosis in the sh-RANBP1 interference group. Conclusion In summary, sh-RANBP1 affects miRNA expression in breast cancer cells, then regulates the expression of mRNA, and ultimately increases the proportion of apoptosis in breast cancer cells.

Resistance risk and mechanism of prochloraz in Fusarium solani - Xuewei Mao; Tangbo Cao; Liting Chen; Min Li; Xingchen Zhao; Hao Liu; Yun Duan; Li Wang; Lin Zhou (Pesticide Biochemistry and Physiology, 2025)

Influence of disaccharide and mixed starter cultures on the fermentation process in earthen jar of factory-produced Sichuan paocai - Qiu Zhong; Hua Xiong; Shengshuai Li; Kaiyu Guo; Yue Shu; Xia Lin; Yage Xing; Ziwei Liang; Xingchen Liu; Lei Liu; Yu Rao (Food Research International, 2025)

Intelligent responsive nanosystem for precision targeting and multimodal imaging-guided high-efficient photothermal therapy against colon cancer - Lei Li; Annan Liu; Hao Liang; Xingchen Li; Maja D. Nešić; Hui Guo; Ze Wang; Quan Lin (Chemical Engineering Journal, 2025)

Flowering in aged white tea: Recovering umami taste and amplifying of stale aroma - Wan Zhu; Xinyu Feng; Yani Pan; Haowei Guo; Yunqing Liu; Xingchen Lin; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2025)

Concentration characteristics and emission estimates of major HCFCs and HFCs at three typical fluorochemical plants in China based on a Gaussian diffusion model - Zehua Liu; Jing Wu; Tengfei Ma; Minde An; Tong Ye; Xingchen Zhao; Mingzhu Li; Fan Wang; Mao Yuan; Dongmei Hu; Yueling Zhang; Lin Peng (Atmospheric Environment, 2024)

MaHOS15 negatively regulates plant immune defense induced by banana fusarium wilt via salicylic acid pathway - Xingchen Jia; Kelin Chen; Yinglong Chen; Yi Tang; Hang Rong; Ping Lin; Yuhao Zhou; Chuqiao Wang; Mingyuan Wang; Jianfu Liu; Qizhi Wang; Hailing Yu (Physiological and Molecular Plant Pathology, 2024)

Golden-flower fungus (Eurotiwm Cristatum) presents fungal flower aroma as well as accelerates the aging of white tea (Shoumei) - Wan Zhu; Su Zhou; Haowei Guo; Jiali Hu; Yanyan Cao; Yingxin Xu; Xingchen Lin; Baoming Tian; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Groundtruthing nitrogen isotopes as a symbiosis proxy using the facultatively symbiotic coral Oculina arbuscula - Heather A. Donnelly; Maria Valadez-Ingersoll; Marcus Lin; Hanny E. Rivera; Carlos A. Tramonte; Sarah W. Davies; Xingchen Tony Wang (Frontiers in Marine Science, 2024)
The resilience of coral reefs in oligotrophic, (sub)tropical oceans is largely due to the symbiotic relationship between scleractinian corals and Symbiodiniaceae algae, which enables efficient internal nutrient recycling. Investigating the history of this coral symbiosis can provide insights into its role in sustaining the health of both present and future coral reefs. The isotopic composition of organic nitrogen ( 15 N/ 14 N or δ 15 N) bound within coral skeletons has been utilized to trace the existence of symbiosis in fossil corals, suggesting that coral symbiosis dates back to at least 210 million years ago. The basis of this proxy is that symbiotic corals are expected to exhibit lower δ 15 N compared to their non-symbiotic (aposymbiotic) counterparts within the same environments, owing to internal nitrogen recycling between the coral host and algal symbiont, and reduced leakage of low-δ 15 N ammonium into seawater. However, this hypothesis has not been adequately tested in contemporary settings. In a laboratory experiment, we examined the δ 15 N differences between the symbiotic and aposymbiotic branches within the same genetic backgrounds of the facultatively symbiotic coral Oculina arbuscula under well-fed conditions. Across five different genotypes in two separate experiments, symbiotic branches consistently showed lower δ 15 N than their aposymbiotic counterparts. These findings corroborate the use of δ 15 N as a proxy for identifying coral symbiosis in the past, particularly when multiple species of corals coexisted in the same environments.

Comparative study on the rock breaking performance of constant cross section disc cutter and inserted tooth disc cutter for cutting granite - Laikuang Lin; Ruiling Li; Xingchen Luo; Yimin Xia (Tunnelling and Underground Space Technology, 2024)

Indirect load measurement method and experimental verification of floating offshore wind turbine - Xiangheng Feng; Yonggang Lin; Yajing Gu; Xingchen Zhao; Hongwei Liu; Yong Sun (Ocean Engineering, 2024)

Glucose-Responsive hydrogel optimizing Fenton reaction to eradicate multidrug-resistant bacteria for infected diabetic wound healing - Xingchen Li; Zifan Meng; Lin Guan; Annan Liu; Lei Li; Maja D. Nešić; Bai Yang; Wenrui Qu; Quan Lin (Chemical Engineering Journal, 2024)

Polygonum cillinerve polysaccharide inhibits transmissible gastroenteritis virus by regulating microRNA-181 - Xueqin Duan; Huicong Li; Xuewen Tan; Nishang Liu; Xingchen Wang; Weimin Zhang; Yingqiu Liu; Wuren Ma; Yi Wu; Lin Ma; Yunpeng Fan (The Veterinary Journal, 2024)

Retraction Note to: Groundwater pollution prevention based on improved particle swarm algorithm and sports training optimization - Zhenggen Lin; Xingchen Fu; Boxiao Gu; Zhemin Fu (Arabian Journal of Geosciences, 2021)

RETRACTED ARTICLE: Groundwater pollution prevention based on improved particle swarm algorithm and sports training optimization - Zhenggen Lin; Xingchen Fu; Boxiao Gu; Zhemin Fu (Arabian Journal of Geosciences, 2021)